Interfacial RAFT Miniemulsion Polymerization: Architectures from an Interface. Issue 12 (7th May 2015) - Fuchs, Adrian V.; Thurecht, Kristofer J.
<x xml:space="preserve">Abstract</x> Directing polymerization from a liquid–liquid interface is an emergent field delivering new insights into polymerization mechanisms, while creating interesting and novel polymer architectures. This review aims to explore how reversible addition–fragmentation chain‐transfer (RAFT) polymerization has been utilized in miniemulsion to perform controlled polymerizations at the biphasic liquid–liquid interface. Highlighted herein are the initial investigations that led to a new class of interfacially active macro‐RAFT agents. These are capable of stabilizing emulsions, directing polymer growth from that interface, and subsequently producing capsule‐like architectures. A comprehensive description is provided concerning the various macro‐RAFT agents employed and the importance of performing this under miniemulsion conditions to obtain either nanoparticles, nanocapsules, and/or core–shell morphologies. Finally, a focus on exciting applications of such systems for the production of nanomaterials including delivery vehicles with stimuli‐responsive properties is presented.